RETRACTED: Methods of formation of business processes of construction enterprises based on the concept of sustainable development - Geraskin Yuri; Nezametdinov Ilgiz; Bogdanov Daniil; Fateeva Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001